Pokrycie terenów zalewowych rzeki warty i poziom ryzyka powodziowego gmin powiatu poznańskiego - Głosińska, Ewa (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The aim of this paper is analysis the cover forms of the Warta river floodplains in the Poznań district and assessment the level of individual community flood risk on the basis of their hierarchy. Also separated group of community with similar structure cover forms of floodplains. The flood risk level of individual community greatly varies depending on the cover form of floodplains.
Keywords: tereny zalewowe; pokrycie terenu; ryzyko powodziowe; floodplains; land cover; flood risk